2002
DOI: 10.1094/pdis.2002.86.8.859
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Fertilizer Applications on Gray Leaf Spot and Yield in Maize

Abstract: The effects of the application of 0, 60, and 120 kg N ha-1 and of 0, 25, 50, and 150 kg K ha-1 on final disease severity, standardized area under disease progress curve, and grain yield were investigated at Cedara, South Africa, on a maize (Zea mays) hybrid susceptible to gray leaf spot (GLS), caused by Cercospora zeae-maydis. The trial was a randomized 3 × 4 factor design, split for fungicide treatments, and replicated three times. With increased N and K levels, final percent leaf blighting and the standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
3
0
3
Order By: Relevance
“…The excess of N may inhibit the production of host defense compounds in response to pathogens infection (HUBER 1980). Caldwell et al (2002) studying the effect of the different rates of N applied in maize observed increase of gray leaf spot for the biggest N rate. Tomato plants that received N application were more susceptible to Oidium lycopersicum (HOFFLAND; JEGER; BEUSICHEM, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The excess of N may inhibit the production of host defense compounds in response to pathogens infection (HUBER 1980). Caldwell et al (2002) studying the effect of the different rates of N applied in maize observed increase of gray leaf spot for the biggest N rate. Tomato plants that received N application were more susceptible to Oidium lycopersicum (HOFFLAND; JEGER; BEUSICHEM, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Esses valores confirmam que, embora exista variabilidade genética quanto à resistência a mancha de Curvularia em ambos os níveis de adubação de cobertura, em condições de alto nível de nitrogênio, a variância genética é superior a observada em baixo N. Com isso, o sucesso de seleção de cultivares resistentes a mancha de Curvularia é mais favorável em alto N. De acordo com Cruz (2006) quanto maior o valor de variância genética maior o sucesso de seleção. Esse maior valor de variância genética em alto N, principalmente na segunda avaliação da mancha de Curvularia pode ser devido a altas doses de nitrogênio favorecer a infecção e o desenvolvimento de doenças fúngicas (Caldwell et al, 2002). Isso pode ter ocorrido devido à alta concentração de nitrogênio nas plantas reduzir a produção de compostos fenólicos (fungistáticos) e de lignina nas folhas, diminuindo a resistência aos patógenos (Marschner, 1986).…”
Section: Resultsunclassified
“…The lowest severity levels were observed at the lowest dose of N, combined to the highest dose of K, and nitrogen fertilization influenced the K content negatively in the upper canopy. Caldwell et al (2002) also report an increase in the severity of cercosporiosis (Cercospora zeae maydis Tehon & Daniels) of corn with increased doses of N (0, 60 and 120 Kg ha -1 ) and K (0, 25, 50 and 150 Kg ha -1 ) in the soil. However, there is still no information about the influence of N and K have upon the maize white spot.…”
Section: Introductionmentioning
confidence: 90%